THE INFLUENCE OF KNOWLEDGE MANAGEMENT, SKILLS AND WORK ATTITUDES ON EMPLOYEE PERFORMANCE PT. SARANA AGUNG SEJAHTERA - Aditya, Moch Iqbal; Fauzi, Akhmad (International Journal of Multidisciplinary Research and Literature, 2025)
This study was carried out with the objective of analyzing the extent to which knowledge management, professional competencies, and work attitudes influence employee performance within PT Sarana Agung Sejahtera. The research population comprised the entire workforce of the company, specifically 33 individuals categorized as permanent employees and an additional 5 individuals classified as non-permanent employees. The study employed a quantitative research approach, utilizing primary data as the principal source of information to ensure empirical validity and reliability in the findings. The process of sample selection was conducted through a probability sampling approach, specifically employing a random sampling technique. This method involved the dissemination of structured questionnaires via the Google Form platform, ultimately yielding a total of 38 respondents who actively participated in the study. To ensure rigorous data analysis, the study utilized the Partial Least Square (PLS) statistical application, incorporating multiple assessment stages, including validity testing to evaluate the accuracy of the measurement instruments, reliability testing to assess data consistency, and hypothesis testing to examine the relationships between the studied variables. The empirical findings of this research indicate that knowledge management, professional competencies, and work attitudes collectively exert a significant influence on enhancing the overall performance of employees at PT Sarana Agung Sejahtera